Some physical and motor abilities and their relationship to the accuracy of the performance of the front and rear driven kick in the badminton for the students of the Faculty of Physical Education and Sports Sciences / Al- Mustansiriyah University - Mahmoud Jassim, Ghada; Qassem Badr, Mohamed (International Journal of Psychosocial Rehabilitation, 2020)
Studies that are concerned with mathematical numbers for various games are one of the studies that take into account the measurement of the physical characteristics of each game in order to be able to provide the trainer and the player with information about these characteristics and to indicate their importance and role in the specificity of this game and the extent of its relationship to the style of play and the application of its basic skills. The game of badminton is one of the Olympic-approved individual games, in which its practice requires the performance of special skills and accurate technical performance, and the physical side has a prominent and important role in many matches, especially when the level is close between the players in terms of planning and skill, and the researchers have noted through their practice of these The game and their observations of the game and the university tournament and the participation of the college teams in it and informing them about the research, they noticed there is a weakness in the accuracy of the front and backstroke among the members of the research sample, which may be due to a weakness in the physical characteristics of this game. Therefore, the researchers decided to study the relationship between these characteristics and the skill of the strike The foreground and the background for the purpose of identifying weaknesses and raising the players to the required level and their goal is clear, and the researchers assumed that there is a statistically significant correlation between some physical and motor abilities and the accuracy of performing some basic skills in badminton among students of the Elected College of Physical Education / Al- Mustansiriyah University, and he chose The two researchers, the research sample consisting of (8) students from the team of the College of Physical Education team The University / AlMustansiriyah University, where the two researchers provided the physical and motor capabilities and physical and skill tests appropriate for the study and presented them to the experts and were identified by them, and the two researchers also processed their research using appropriate statistical means. The two researchers also presented, analyzed and discussed the results they obtained from the research tests and reached There is a moral correlation between some physical abilities and the accuracy of performing the front and back blow with the badminton, and the two researchers also recommended the necessity to emphasize the interest in training programs and tests developed for the players must be correct and appropriate to the capabilities of the players and add to them benefit.